2018
DOI: 10.1039/c8cc06010j
|View full text |Cite
|
Sign up to set email alerts
|

A halogen bond-donor amino acid for organocatalysis in water

Abstract: Herein we report a halogen bond-donor amino acid, 4-iodotetrafluorophenylalanine, which behaves as a catalyst for the aqueous synthesis of bis-(heterocyclic)methanes. We also provide experimental evidence that halogen bonding is a plausible explanation for the observed catalytic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 38 publications
0
25
0
1
Order By: Relevance
“…Thus, we consider the reported crystal structures as a reasonable model of the resulting interaction pattern in the presence of highly polarizable halogen atoms. Considering strength and high directionality of halogen bonding, halogenation is not yet fully exploited as a supramolecular tool in the context of peptide‐based nanotechnologies; however, we feel that all the potential showed by halogenation will unlock new and valuable opportunities for the scientific community, as shown in the field of catalysis and in the synthesis of hybrid metal‐peptide nanostructures …”
Section: Resultsmentioning
confidence: 99%
“…Thus, we consider the reported crystal structures as a reasonable model of the resulting interaction pattern in the presence of highly polarizable halogen atoms. Considering strength and high directionality of halogen bonding, halogenation is not yet fully exploited as a supramolecular tool in the context of peptide‐based nanotechnologies; however, we feel that all the potential showed by halogenation will unlock new and valuable opportunities for the scientific community, as shown in the field of catalysis and in the synthesis of hybrid metal‐peptide nanostructures …”
Section: Resultsmentioning
confidence: 99%
“…In the early proof-of-principle stage of halogen bond catalysis, starting from the pioneering work of Bolm et al (Scheme 1) [16], mechanistic studies were almost exclusively conducted in experiments. The catalysts' ability to form halogen bonds was unambiguously established via X-ray crystallography studies [19][20][21][22][23][24][25][26][27][28][29], which clearly showed the close contacts between halogen atoms and counter anions in the case of ionic catalysts, or other XB-acceptors in the case of neutral ones. In addition, NMR studies allowed probing the interaction between XB catalysts and substrates in various organic solvents [30,31].…”
Section: Introductionmentioning
confidence: 97%
“…结合受限路易斯酸碱对对醛酮的催化反应研究, 以 及实验室对有水条件下 FLPs 对醛酮的直接还原胺化反 应机理的研究发现 [45] , 本文利用硅烷作为还原剂, 系统 [46] , 即 可 能 存 在 " PhCH = O---H-O(-H)---B(C 6 F 5 ) 3 "的三组分络合形式. 在 B3LYP [47,48] 行了结构优化和振动频率分析, 计算采用 Gaussian 16 程序包 [49] .…”
unclassified